Inter-religious Harmony between Hindu Muslim Groups in Nepal - Ojha, Niranjan (Interdisciplinary Journal of Management and Social Sciences, 2021)
Religious harmony is very important to maintain peace and stability in a country like Nepal where people are multi-religious. Failure to address religious harmony it could take the society into conflict. Though Nepal is a Hindu dominant secular country the Muslims are an important and inseparable part of Nepalese community. They have been living in Nepal since last 500 years with religious harmony. During this period there were negligible religious riots between Hindu and Muslims. Social acceptance and recognition given to the Nepali Muslims, they were integrated in such a way, became inseparable part of the society. But in recent years they have tried to differentiate themselves religiously challenging centuries old harmony and peace. In the process they have undergone a process of political Islamization and have emerged as a distinctive ethnic community. It has shown a danger of deadly encounter between Hindu-Muslim religion groups. This paper tries to discuss the fundamental factors contributing to religious in a multi-religious society. FGD and library research method is used in addressing the situation of religious harmony. This paper also emphasizes that elements such as acceptance, understanding, co-operation as well as right and justice are significant elements in sustaining religious harmony. Hence, the discussion is aimed to build a sustainable concept of multi-religious harmony in Nepal. The findings could encourage maintaining strong relationship among them.